Aktivitas Antibakteri Ekstrak Etanol Daging Buah Beligo (Benincasa hispida (Thunb.) Cogn.) terhadap Escherichia coli dan Staphylococcus aureus - Hasanuddin, Rusman; Alim, Nur; Jasmiadi; Fauzan, Ahmad (Jurnal Novem Medika Farmasi, 2023)
Antibacterial is a compound that can be used to inhibit or kill bacteria. Ethanol extract of Beligo fruit flesh [Benincasa hispida (Thunb.) Cogn.)] contains flavanoid compounds that can be used as antibacterials. The purpose of this research was to determine the antibacterial activity of the ethanol extract of beligo fruit flesh [Benincasa hispida (Thunb.) Cogn.)] against bacteria Escherichia coli and Staphylococcus aureus. Research methods include macerated extraction using 70% ethanol and testing antibacterial activity against bacteria Escherichia coli and Staphylococcus aureus with diffusion methods using disc paper. The result obtained using concentration of 12,8%; 25,6%; 51,2% each had an inhibitory diamter of 7,34 mm; 8,97 mm; 12,12 mm for Staphyloccous aureus bacteria while the inhibitory diamter is 6,45 mm; 7,33 mm; 9,91 mm for Escherichia coli bacteria. The conclusion of this research is that the ethanol extract of Beligo fruit flesh has antibacterial activity against Escherichia coli and Staphylococcus aureus.